KEUNGGULAN DAN MANFAAT SERTIFIKASI LOGO HALAL PRODUK KOSMETIK (IAIN Tulungagung, 2023)
The background of the problem with globalization, free trade and the Asian Economic Community (AEC) has led to an increase in the circulation of cosmetic products in Indonesian society. Indonesia is a country with the largest Muslim population in the world. In Article 29 paragraph (2) of the 1945 Constitution of the Republic of Indonesia it is stated that